Контекстуально-ситуативний режим інтерпретації тексту: спроба обґрунтування - Бацeвич Флoрій (Slavia Orientalis, 2026)
The article clarifies the concept of the ‘mode of text interpretation’ and defines its place within the system of research procedures (method, methodology, and technique). Drawing on examples of informational and advertising-informational messages, the study substantiates the appropriateness of introducing the concept of the ‘contextual-situational mode of interpretation’ as a research procedure that accounts for various explicit and implicit socio-political, cultural, temporal, spatial, qualitative, quantitative, and other factors influencing the perception of a particular text, as well as the functional features of its units and categories, whose communicative meaning is explicated by the researcher. Demonstrated is that the use of the contextual-situational mode of interpretation for the analysis of informational and advertising-informational texts makes it possible to refine the semantics of several nominative units – in particular, the communicative meanings of deictic elements that are deeply integrated into the situation and context of usage. Moreover, this approach helps explicate and systematise presuppositions underlying the semantic structure of such textual messages: those set by the addresser and those determined by the interpreter. These are primarily existential presuppositions – those concerning the existence and key functions of referential objects at a particular time and in a specific place – as well as the refinement of the semantic content of the categories of place, time, quantity, quality, among others. The prospect of further elaborating the concept of the mode of interpretation and its varieties lies in expanding the research potential of this analytical strategy and applying it to the analysis and typology of communicative meanings in texts of various functional and genre realisations. The contextual-situational mode of interpretation may be an effective tool for analysing discourses and intertextual connections, together with their corresponding implicit communicative meanings grounded in historical, ethnocultural, aesthetic, ethical, and other presuppositions.